2014
DOI: 10.3109/02713683.2014.952831
|View full text |Cite
|
Sign up to set email alerts
|

Dye Solutions Based on Lutein and Zeaxanthin:In VitroandIn VivoAnalysis of Ocular Toxicity Profiles

Abstract: L/Z-based dye solutions demonstrated a safe profile in in vitro and in vivo models, and may be a useful tool for staining intraocular structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Mein used ferret BCO2 as a model to study the enzymatic formation of apo-carotenoids from lutein, zeaxanthin, and β-cryptoxanthin and identified both volatile and non-volatile apo-carotenoid products including 3-OH-β-ionone, 3-OH-α-ionone, β-ionone, 3-OH-α-apo-10′-carotenal, 3-OH-β-apo-10′-carotenal, and β-apo-10′-carotenal (Mein et al, 2011). Rabbits tissues were used to study the in-vitro toxicity profile of lutein and zeaxanthin-based dye solutions (Casaroli-Marano et al, 2015). They did not see any structural alterations in the neurosensory retina, RPE, or choroidal complex.…”
Section: Basic Science Of the Macular Pigment Carotenoidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mein used ferret BCO2 as a model to study the enzymatic formation of apo-carotenoids from lutein, zeaxanthin, and β-cryptoxanthin and identified both volatile and non-volatile apo-carotenoid products including 3-OH-β-ionone, 3-OH-α-ionone, β-ionone, 3-OH-α-apo-10′-carotenal, 3-OH-β-apo-10′-carotenal, and β-apo-10′-carotenal (Mein et al, 2011). Rabbits tissues were used to study the in-vitro toxicity profile of lutein and zeaxanthin-based dye solutions (Casaroli-Marano et al, 2015). They did not see any structural alterations in the neurosensory retina, RPE, or choroidal complex.…”
Section: Basic Science Of the Macular Pigment Carotenoidsmentioning
confidence: 99%
“…They did not see any structural alterations in the neurosensory retina, RPE, or choroidal complex. These xanthophyll-based dye solutions have proven to be safe and can be used to stain intraocular structures in rabbits (Casaroli-Marano et al, 2015). Rabbits have also been used to study the absorption and distribution of carotenoids in plasma, liver, and adrenal glands(Yap et al, 1997).…”
Section: Basic Science Of the Macular Pigment Carotenoidsmentioning
confidence: 99%
“…Specifically for Retidyne, these results suggest a nonchemical bonding to the membrane and are in agreement with previous preclinical and clinical tests that showed that this natural dye is safe to be used intraocularly. 22,24,26,28 However, the results for BB do not correlate completely with reports that showed dose-and timedependent toxicity of this dye in retinal cell lines, revealing that it is prudent to use the lowest possible concentration during the surgery. 34,35 When analyzing the behavior of Retidyne Plus while in contact with the same model, we observed a change in the isotherm of ILM model.…”
Section: Discussionmentioning
confidence: 66%
“…[19][20][21] In our previous publications, we have described the use of novel intraocular dyes in which Lutein is the primary component in cataract and vitreoretinal surgeries. [22][23][24][25][26][27][28] These L/Z-based dyes have shown efficacy in staining target membranes such as AC, ILM, and the vitreous, as well as an excellent safety profile. [22][23][24][25][26][27][28] The nature of the interaction of L/Z-based dyes with their target membranes is herein investigated using Langmuir monolayer models simulating the ILM, vitreous, AC, and epiretinal membrane (ERM).…”
mentioning
confidence: 99%
“…Since then, studies have continued to look at lutein and its effects on the retina. A recent study by Casaroli-Marano et al [9], in 2015, demonstrated that there was no evidence of structural alterations in the neurosensory retina, retinal pigmented epithelium (RPE), or choriocapillaris-choroidal complex caused by dye solutions based on lutein and zeaxanthin.…”
Section: Introductionmentioning
confidence: 99%